Rho GTPases: Regulation and roles in cancer cell biology. (1st October 2016) - Haga, Raquel B.; Ridley, Anne J.
ABSTRACT: Rho GTPases are well known for their roles in regulating cell migration, and also contribute to a variety of other cellular responses. They are subdivided into 2 groups: typical and atypical. The typical Rho family members, including RhoA, Rac1 and Cdc42, cycle between an active GTP-bound and inactive GDP-bound conformation, and are regulated by GEFs, GAPs and GDIs, whereas atypical Rho family members have amino acid substitutions that alter their ability to interact with GTP/GDP and hence are regulated by different mechanisms. Both typical and atypical Rho GTPases contribute to cancer progression. In a few cancers, RhoA or Rac1 are mutated, but in most cancers expression levels and/or activity of Rho GTPases is altered. Rho GTPase signaling could therefore be therapeutically targeted in cancer treatment.